The Calamity Among Medical Students: Sleep Deprivation and Dry Eye Disease - Salim, Anastasia Johanna; Salim, Jonathan; Josiah Irma, Josiah x (Fakultas Kedokteran Universitas Pelita Harapan, 2022)
Background: Medical students’ burden upon academic and professional duties often blinded them from attending to themselves. Piling works and nightshifts interfere ferociously with their self-care behavior, including adequate sleep. The matter not only disrupts concentration and consciousness but also tolls the eye by reducing tear secretion. Hence, the present study urgently assesses sleep quality and dry eye disease (DED) among medical students.Methods: The cross-sectional study observed 172 eyes among medical students in Indonesia. We assessed sleep quality and dry eye disease through Pittsburgh Sleep Quality Index and Schirmer test. Independent statistician analyzed the data with chi-square.Result: From the eligible samples, there is a dominancy of females (55.8%) with poor sleep quality (55.2%). There is no significant difference in DED or sleep quality across gender though they lean toward females. Contrarily, poor sleepers significantly correspond to 2.96 times more risk of DED than an adequate sleeper.Conclusions: Medical students’ well-being is crucial. Aside from the academic burden, institutions and individuals shall strongly emphasize better sleep habits and eye care.